Delipidation of Plasma Has Minimal Effects on Human Butyrylcholinesterase - Onder, Seda; Tacal, Ozden; Lockridge, Oksana (Frontiers in Pharmacology, 2018)
Human butyrylcholinesterase (BChE) is purified in large quantities from Cohn fraction IV-4 to use for protection against the toxicity of chemical warfare agents. Small scale preliminary experiments use outdated plasma from the American Red Cross as the starting material for purifying BChE (P06276). Many of the volunteer donor plasma samples are turbid with fat, the donor having eaten fatty food before the blood draw. The turbid fat interferes with enzyme assays performed in the spectrophotometer and with column chromatography. Our goal was to find a method to remove fat from plasma without loss of BChE activity. Satisfactory delipidation was achieved by adding a solution of 10% dextran sulfate and calcium chloride to fatty plasma, followed by centrifugation, and filtration through a 0.8 µm filter. Treatment with Aerosil also delipidated fatty plasma, but was accompanied by loss of 50% of the plasma volume. BChE activity and the BChE isozyme pattern on nondenaturing gel electrophoresis were unaffected by delipidation. BChE in delipidated plasma was efficiently captured by immobilized monoclonal antibodies B2 18-5 and mAb2. The immunopurified BChE was released from antibody binding with acid and visualized as a highly enriched, denatured BChE preparation by SDS gel electrophoresis. In conclusion, delipidation with dextran sulfate/CaCl2 preserves BChE activity and the tetramer structure of BChE.